2013
DOI: 10.1155/2013/617943
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone-Induced Cirrhosis of Liver: What Predicts Mortality?

Abstract: Introduction. Amiodarone has been used for more than 5 decades for the treatment of various tachyarrhythmias and previously for the treatment of refractory angina. There are multiple well-established side effects of amiodarone. However, amiodarone-induced cirrhosis (AIC) of liver is an underrecognized complication. Methods. A systematic search of Medline from January 1970 to November 2012 by using the following terms, amiodarone and cirrhosis, identified 37 reported cases of which 30 were used in this analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Serum enzyme elevations are reported to occur in 15% to 50% of patients on long term therapy. However, with lower doses (200 mg to 300 mg daily), ALT elevations are less common [4]. Also, pre-existing liver dysfunction was not predictive of transaminitis in a population of 720 Chinese patients.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Serum enzyme elevations are reported to occur in 15% to 50% of patients on long term therapy. However, with lower doses (200 mg to 300 mg daily), ALT elevations are less common [4]. Also, pre-existing liver dysfunction was not predictive of transaminitis in a population of 720 Chinese patients.…”
Section: Discussionmentioning
confidence: 85%
“…In a 2013 study by Hassain et al a MEDLINE search from 1970 to 2012 found only 37 reported cases of amiodarone associated with cirrhosis [4]. They also revealed that Aspartate aminotransferase was significantly lower (P = 0.03) in patients who survived at 5-months (mean 103.33 IU/L) compared to non-survivors (mean 216.88 IU/L) and demonstrated that amiodarone associated cirrhosis carried a mortality risk of 60% at 5 months once the diagnosis was established [4].…”
Section: Discussionmentioning
confidence: 99%
“…In the group of amiodarone patients, VNC led to a mean decrease of LAI of around 10 HU compared to TNC, potentially representing artificially high attenuation in TNC from the iodine in amiodarone. This difference can be relevant in amiodarone patients when it obscures potential liver damage reflected by liver steatosis 1,7,8 . The LAI is predictive for a liver fat fraction of >30% and image-based diagnosis of liver steatosis when the difference is less than −10 HU 39-41 , hence a mean difference of 10 HU could possibly lead to many misclassified patients.…”
Section: Resultsmentioning
confidence: 99%
“…Amiodarone concentrations in the liver can be up to 500-times higher than in the blood serum and release from hepatocytes is slow after treatment discontinuation 1-6 . Earlier studies found that this condition can lead to steatohepatitis and liver cirrhosis 1,7,8 .…”
mentioning
confidence: 98%
See 1 more Smart Citation